2015
DOI: 10.1038/nm.3776
|View full text |Cite
|
Sign up to set email alerts
|

A C-terminal HSP90 inhibitor restores glucocorticoid sensitivity and relieves a mouse allograft model of Cushing disease

Abstract: One function of the glucocorticoid receptor (GR) in corticotroph cells is to suppress the transcription of the gene encoding proopiomelanocortin (POMC), the precursor of the stress hormone adrenocorticotropin (ACTH). Cushing disease is a neuroendocrine condition caused by partially glucocorticoid-resistant corticotroph adenomas that excessively secrete ACTH, which leads to hypercortisolism. Mutations that impair GR function explain glucocorticoid resistance only in sporadic cases. However, the proper folding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
95
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 41 publications
5
95
0
2
Order By: Relevance
“…In addition, information is missing on the role of USP8 mutational status in the development of resistance to glucocorticoid feedback inhibition, a hallmark of CD. Glucocorticoid resistance is mainly due to deregulated glucocorticoid receptor transrepression regulation and chaperon proteins, but the responsible genetic defects remain for the most part unclear (74,75). Altogether, the finding in CD tumors of a single mutational hotspot on the USP8 gene that encodes for an important regulator of protein stability and function serves as a focal point for the better understanding of corticotroph tumor development and the development of effective tumor-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, information is missing on the role of USP8 mutational status in the development of resistance to glucocorticoid feedback inhibition, a hallmark of CD. Glucocorticoid resistance is mainly due to deregulated glucocorticoid receptor transrepression regulation and chaperon proteins, but the responsible genetic defects remain for the most part unclear (74,75). Altogether, the finding in CD tumors of a single mutational hotspot on the USP8 gene that encodes for an important regulator of protein stability and function serves as a focal point for the better understanding of corticotroph tumor development and the development of effective tumor-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The relative insensitivity of pituitary POMC to Gc is indeed used as a discriminating clinical test to diagnose Cushing's disease (Liddle 1960). The cause of Gc resistance in corticotroph adenomas of patients with Cushing's disease was very rarely ascribed to GR mutations (Lamberts 2002), but processing of GR may be altered in a subset of adenomas that overexpress the chaperone HSP90 (Riebold et al 2015). Rather, it is often the Gc-dependent corticotroph response mechanisms that are altered.…”
Section: Glucocorticoid Repression Of Pomc and Cushing's Diseasementioning
confidence: 99%
“…In a mouse allograft model of Cushing's disease, silibinin was shown to lower ACTH and corticosterone levels, thus partially overcoming glucocorticoid resistance and relieving the symptoms of Cushing's disease. 143 These findings reveal a new pharmacological mechanism of action for a select class of Hsp90 inhibitors that might be used to restore glucocorticoid sensitivity in ACTH-secreting adenomas in individuals with Cushing's syndrome.…”
mentioning
confidence: 93%
“…142 Recent studies have revealed the overexpression of Hsp90α and β isoforms in glucocorticoid-resistant corticotroph adenomas in comparison to normal pituitary. 143 Pharmacological inhibition of Hsp90 with the N-terminal Hsp90 inhibitor, 17AAG, a derivative of geldanamycin and the C-terminal inhibitory reagents, novobiocin and silibinin, an analog of the natural product, silymarin, 144 showed vastly different outcomes for GR activity when used at low concentrations. 143 Thus, 17AAG promoted GR degradation in a corticotroph cell line, whereas novobiocin and silibinin, which act at a different stage of the Hsp90 chaperoning cycle, caused a release of mature, correctly folded GR from Hsp90 that was capable of hormone binding and transcriptional activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation